MAp34 Regulates the Non-specific Cell Immunity of Monocytes/Macrophages and Inhibits the Lectin Pathway of Complement Activation in a Teleost Fish - Mu, Liangliang; Yin, Xiaoxue; Wu, Hairong; Han, Kailiang; Guo, Zheng; Ye, Jianmin (Frontiers in Immunology, 2020)
The lectin pathway of the complement system is one of the main components of innate immunity, which plays a pivotal role in the defense against infectious microorganisms and maintains immune homeostasis. However, its control mechanisms remain unclear in teleost fish. In this study, we described the identification and functional characterization of a mannose-binding lectin associated protein MAp34 (OnMAp34) from Nile tilapia (Oreochromis niloticus) at molecular, cellular and protein levels. The open reading frame (ORF) of OnMAp34 is 918 bp of nucleotide sequence encoding a polypeptide of 305 amino acids. The deduced amino acid sequence has three characteristic structures, including two C1r/C1s-Uegf-BMP domains (CUB) and one epidermal growth factor domain (EGF). Expression analysis revealed that the OnMAp34 was highly expressed in liver, and widely existed in other examined tissues. In addition, the mRNA and protein expression levels of OnMAp34 were remarkably altered upon infection with Streptococcus agalactiae and Aeromonas hydrophila in vivo and in vitro. Further, we found that the OnMAp34 could participate in the non-specific cellular immune defense, including the regulation of inflammation, migration, and enhancement of phagocytosis of monocytes/macrophages. Moreover, the OnMAp34 could compete with OnMASPs to combine OnMBL, and inhibit the lectin pathway of complement activation. Overall, our results provide new insights into the understanding of MAp34 as a potent regulator in the lectin complement pathway and non-specific cell immunity in an early vertebrate.